Factors Affecting Students' Interest in Learning Dance in MTs Negeri 1 Prabumulih City - Sari, Rita Puspita; Idris, Muhamad; Setyaningrum, Naomi Diah Budi (CV. Rayyan Dwi Bharata, 2022)
This study aims to determine what factors influence students' interest in learning dance in the teaching and learning process. This research is a qualitative research, the research population is class VII 5 MTs Negeri 1 Prabumulih with a total of 31 students. Data obtained from the distribution of questionnaires, interviews, and observations. Results Based on observations at school there are still many students who are less interested in learning dance. This situation is caused by several factors, namely intrinsic factors and extrinsic factors. Intrinsic factors are factors that come from within the individual and can affect student learning outcomes, for example physical factors, physical, intelligence, interests and talents. While extrinsic factors are factors that come from outside the individual and can affect learning outcomes, for example family, school, and community factors. It can be said that these factors have a considerable influence on students' interest in learning art. There should be cooperation between teachers, schools, and families to increase students' interest in learning dance.